Intestinal Parasitic Infections as Public Health Problem among School Children - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2022)
Infections by intestinal parasites are a major public health problem and socio-economic issue worldwide, particularly among children in rural communities with poor sanitation. These infections affect child health and development and result in growth and cognitive delays in the long term. The transmission of intestinal parasites is affected directly or indirectly by objects contaminated with feces. In addition, agriculture and food production (e.g., raw vegetables) can be a major source of parasitic infections. In this issue, Edrees et al. report that intestinal parasitic infection was found among 61.85% of primary school children, comprising 63.63% in public schools, and 60% in private schools. A high incidence of intestinal parasites among school children suggests the launch of intervention programs including health education and environmental sanitation.